Effect of borage and green tea aqueous extracts on the quality of lamb leg chops displayed under retail conditions. (July 2017) - Bellés, M.; Alonso, V.; Roncalés, P.; Beltrán, J.A.
Abstract: Different concentrations of two aqueous extracts from green tea leaves and borage seeds with potential antioxidant activity were evaluated in lamb leg chops. Chops were sprayed with 0.005, 0.05, 0.5, 5% (p/v) green tea extracts (T) and 0.5, 5 and 10% (p/v) borage seed extracts (B) and displayed under retail conditions for 13 days. Total polyphenols, TBARS, colour, microbial and sensory analyses were performed. The extracts showed a concentration-dependent action; the minimum concentration of polyphenols which significantly reduced lipid oxidation was 2.08 mg GAE/100 cm 2 of meat. Both 0.5% T and 10% B limited colour deterioration, reducing also metmyoglobin formation. The extracts showed no antimicrobial effect, exceeding microbial counts of 7 log CFU/cm 2 at 13 days of display. Sensory analyses determined that none of the extracts added herb odours or flavours to lamb. In conclusion, 0.5% T or 10% B extracts extended lamb shelf life from 8 to 11 days, so both would be recommended for lamb chops preservation. Highlights: Green tea and borage seeds aqueous extracts have been developed. The extracts showed a concentration-dependent antioxidant action. Tea (0.5%) and borage (10%) extracts limited lipid oxidation and discolouration. The extracts did not show any antimicrobial effect. Tea (0.5%) and borage extracts (10%) extended lamb shelf life from 8 to 11 days.